THE USE OF TELEMEDICINE IN PRIMARY HEALTHCARE SERVICES IN JAKARTA - Digambiro, Reza Aditya; Ilona, Florinda; Setyaningrum, Dyah Ayu Woro; Chendrasari, Julian; Lestari, Indah Widya (HEARTY, 2025)
Background: The advancement of digital technology has transformed the healthcare sector, and telemedicine has become an important innovation in providing remote clinical services. Methods: The research method used is a mixed-method approach, combining quantitative and qualitative approaches. Data collection was conducted through questionnaires distributed to 400 telemedicine users. The sample size was determined using the Slovin formula with a 5% margin of error. Results: 75% of respondents used telemedicine more than once in the past year, with 70% of respondents expressing high satisfaction with the services received. The main reasons for using telemedicine include convenience (65%) and time savings. However, several challenges were identified, such as technical issues (30%), lack of physical examinations, and concerns about service quality. Discussion: The main challenges identified include inadequate technological infrastructure, low digital literacy among certain groups, and unclear regulations. Development opportunities include the integration of telemedicine with electronic health records and increased public education. Conclusion: Telemedicine has great potential to improve the accessibility and efficiency of healthcare services in Jakarta. However, improvements in infrastructure, digital literacy, and supportive regulatory frameworks are needed to maximize the benefits of telemedicine within the healthcare system.